2017
DOI: 10.4254/wjh.v9.i17.791
|View full text |Cite
|
Sign up to set email alerts
|

Use of aspartate aminotransferase to platelet ratio to reduce the need for FibroScan in the evaluation of liver fibrosis

Abstract: AIMTo evaluate the performance of aspartate aminotransferase to platelet ratio (APRI) score against FibroScan in predicting the presence of fibrosis.METHODSData of patients who concurrently had APRI score, FibroScan and liver biopsy to assess their hepatitis C virus (HCV) and hepatitis B virus (HBV) over 6 years were retrospectively reviewed and details of their disease characteristics and demographics were recorded. Advanced fibrosis was defined as ≥ F3.RESULTSOf the 3619 patients (47.5 ± 11.3 years, 97M:36F)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 24 publications
0
13
0
2
Order By: Relevance
“…It is not unusual for threshold values to differ between published data. Differences in patient populations, including the prevalence of significant fibrosis, cirrhosis, and reference ranges used for AST and ALT levels, may explain these discrepancies [17]. Our data included a large number of patients with advanced fibrosis (63.5%) or cirrhosis (46%), quite a high proportion compared to literature data.…”
Section: Discussionmentioning
confidence: 99%
“…It is not unusual for threshold values to differ between published data. Differences in patient populations, including the prevalence of significant fibrosis, cirrhosis, and reference ranges used for AST and ALT levels, may explain these discrepancies [17]. Our data included a large number of patients with advanced fibrosis (63.5%) or cirrhosis (46%), quite a high proportion compared to literature data.…”
Section: Discussionmentioning
confidence: 99%
“…Liver biopsy is considered the criterion standard for determination of the stages of fibrosis in chronic liver diseases; however, it is difficult to perform or repeat in clinical practice [ 33 ]. Several non-invasive markers have been applied in clinical practice to evaluate the stage of fibrosis in liver diseases [ 22 , 34 ]. In recent years, FibroScan has been thoroughly investigated and has been shown to successfully detect fibrosis in chronic hepatitis [ 23 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…9 Study conducted Wong et al, on 3619 patients on Hepatitis B and Hepatitis C infected Patients and concluded that APRI score is a good marker and can be used as alternate noninvasive marker in predicting fibrosis of liver. 16…”
Section: Discussionmentioning
confidence: 99%